2003
DOI: 10.1136/ard.62.5.400
|View full text |Cite
|
Sign up to set email alerts
|

Suprascapular nerve block (using bupivacaine and methylprednisolone acetate) in chronic shoulder pain

Abstract: Background: Shoulder pain from inflammatory arthritis and/or degenerative disease is a common cause of morbidity in the community. It is difficult to treat and there are limited data on the efficacy of most interventions. Suprascapular nerve block has shown promise in limited trials in reducing shoulder pain. There have been no large randomised placebo controlled trials examining the efficacy of suprascapular nerve block for shoulder pain in arthritis and/or degenerative disease using pain and disability end p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
129
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 21 publications
6
129
1
5
Order By: Relevance
“…8,9 Carette et al and Siraj, et al had similar results for intra-articular steroid. 10,11 In our study it was clearly seen that there is definite efficacy of both, supra-scapular nerve block and intraarticular shoulder steroid injection, in treatment of frozen shoulder.…”
Section: Discussionsupporting
confidence: 69%
“…8,9 Carette et al and Siraj, et al had similar results for intra-articular steroid. 10,11 In our study it was clearly seen that there is definite efficacy of both, supra-scapular nerve block and intraarticular shoulder steroid injection, in treatment of frozen shoulder.…”
Section: Discussionsupporting
confidence: 69%
“…There are comparatively fewer studies of SSNB than SI. It has been studied in glenohumeral arthritis (Brown et al 1988), frozen shoulder (Karatas and Meray 2002), rheumatoid arthritis and osteoarthritis (Gado and Emery 1993;Shanahan et al 2003), hemiplegic shoulder (Lee and Khunadorn 1986), rotator cuff lesions (Vecchio et al 1993) and found to be effective in these clinical pictures. Up to our knowledge, we are the first comparing the effects of these two interventions in non-specific shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…4 It is also an effi cient alternative for patients who cannot undergo surgery. 8 A relative indication would be for patients with advancedstage shoulder tumors, with a level of pain diffi cult to treat and who would benefi t from interventional techniques, among which are SSNB, as it seems very effective and with low rates of adverse effects. In this case, the method works as palliative care, as it treats the symptoms without necessarily having an effect on the cause.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The procedure has been increasingly used in severe pain control and postoperative analgesia after shoulder surgery, [4][5][6][7] as other therapeutic options such as anti-infl ammatory drugs and intra-articular steroid injections have their limitations, mainly in the elderly population, which has many comorbidities. 4,8 The SSNB is a safe, simple, inexpensive procedure, applicable to the majority of physicians working with pain management, 9 in addition to being well tolerated even by patients with several pathologies that affect the shoulder region. 4 It is also an effi cient alternative for patients who cannot undergo surgery.…”
Section: Introductionmentioning
confidence: 99%